On Recidivism: A Commentary on Altier, Boyle, and Horgan - Sageman, Marc (Terrorism and political violence, 2021)
Altier, Boyle, and Horgan claim a 64.6 percent terrorist recidivism rate. However, the unrepresentativeness of their sample, a confusion between the notions of a recidivism base rate and the percentage of recidivists in a sample, and a questionable concept of a global terrorist population undermine their claim.